2002
DOI: 10.1002/bit.10450
|View full text |Cite
|
Sign up to set email alerts
|

Distributed model of solid waste anaerobic digestion: Effects of leachate recirculation and pH adjustment

Abstract: A distributed model of solid waste digestion in a 1-D bioreactor with leachate recirculation and pH adjustment was developed to analyze the balance between the rates of polymer hydrolysis/acidogenesis and methanogenesis during the anaerobic digestion of municipal solid waste (MSW). The model was calibrated on previously published experimental data generated in 2-L reactors filled with shredded refuse and operated with leachate recirculation and neutralization. Based on model simulations, both waste degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(57 citation statements)
references
References 23 publications
2
50
0
2
Order By: Relevance
“…The experiment does not reflect a longterm adaptation to temperatures near 20 °C (or in thermophilic range). In the present study such adaptation has occurred and, moreover, when leachate BOD fell below 20 mgL -1 (L/S 1) indicating very low VFA concentrations, hydrolysis was the rate limiting step, as can be seen in [30]. Consequently a temperature coefficient related to the hydrolysis can be expected and the findings of this study are close to the value given in [29].…”
Section: Post-closure Management and Temperature Impact Coefficientssupporting
confidence: 85%
“…The experiment does not reflect a longterm adaptation to temperatures near 20 °C (or in thermophilic range). In the present study such adaptation has occurred and, moreover, when leachate BOD fell below 20 mgL -1 (L/S 1) indicating very low VFA concentrations, hydrolysis was the rate limiting step, as can be seen in [30]. Consequently a temperature coefficient related to the hydrolysis can be expected and the findings of this study are close to the value given in [29].…”
Section: Post-closure Management and Temperature Impact Coefficientssupporting
confidence: 85%
“…The process following assimilation of acidified substrate led to cell growth of acetogenic/methanogenic bacteria and production of biogas (methane and carbondioxide). Similar process of lumping acetogenic/methanogenic bacteria was reported by Vavilin et al [37] and Vavilin and Angelidaki [38] for modeling anaerobic digestion of solid waste.…”
supporting
confidence: 60%
“…However, in situations where models attempt to account for the nature of complex feedstock, they were restricted to particular substrate such as liquid manure [12,13], sewage sludge [14] or biological waste [15].…”
Section: Introductionmentioning
confidence: 99%
“…Optimal conditions are difficult to be determined and to be fulfilled at farm-scale, which increases the risk of incomplete degradation in this simple fermenter type with no substrate mixing. It has been demonstrated that during process initiation discontinuous leachate recirculation is more favourable than continuous watering (Kusch et al, 2012;Martin, 1999;Vavilin et al, 2002Vavilin et al, , 2003Veeken and Hamelers, 2000), which is assumed to be the result of encouraging methanogenic areas to expand throughout the whole digester, while continuous watering bears the risk to spread acidification. In addition, it was demonstrated that for the process type discussed here there is no beneficial effect of continuous water circulation compared to discontinuous watering throughout the whole digestion process (Kusch et al, 2012).…”
Section: Resultsmentioning
confidence: 99%